Analisis Komparasi Pendapatan Usahatani Karet Pada Sistem Bagi Hasil Di Kecamatan Mestong Kabupaten Muaro Jambi - Sarah Nasution, Siti; Mara, Armen; Yanita, Mirawati (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2022)
This study aims to: 1) determine the description of rubber farming on the profit sharing system in Mestong District, Muaro Jambi Regency, 2) examine the implementation of the rubber farming profit sharing system in Mestong District, Muaro Jambi Regency, 3) analyze rubber farming income on the profit sharing system in the Mestong, Muaro Jambi Regency, 4) analyze the differences in rubber farming income received by share farmers on the profit sharing system in Mestong District, Muaro Jambi Regency. This research was conducted in Mestong District, Muaro Jambi Regency, namely Pondok Meja Village and Sungai Landai Village. Respondent farmers in this study were rubber farmers who carried out a profit sharing system as many as 60 people with the division of 30 rubber farmers on a two-sharing system and 30 rubber farmers on a three-sharing system. The data analysis method used is descriptive and quantitative analysis consisting of income analysis and comparative analysis with the two-average difference test. The results showed that: 1) rubber farming in a double-division system was better than rubber farming in a triple-division system in terms of differences in plant age, production, output prices, use of fertilizers and herbicides, 2) implementation of a profit sharing system in rubber farming in the Mestong District differs in the system, namely the two-sharing system and the three-sharing system, where in its implementation there are differences with the profit sharing concept used, 3) the income of rubber farming in the two-sharing system is 15.34% bigger than the income of rubber farming in the three-sharing system with the difference is Rp. 4,554,595/ha/year, 4) there is no significant difference in the rubber farming income received by the share farmers in the two-sharing system and the triple-sharing system due to the balance of the results and the difference in land conditions in the two profit sharing systems